1975
DOI: 10.1136/gut.16.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Rectal potential difference in the diagnosis of aldosterone excess.

Abstract: SUMMARY Rectal potential difference (pd) is directly related to the plasma aldosterone concentration, and rises when aldosterone is stimulated by sodium deprivation. However, when the measurement of rectal pd was tested at a screening test for hyperaldosteronism in 19 hypertensive subjects, four of the eight with primary hyperaldosteronism had a normal pd and four of the eight without aldosterone excess had an abnormally raised potential difference. The technique cannot therefore be recommended as a routine sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
2
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
4
2
0
Order By: Relevance
“…In control subjects, the basal values of rectal pd generally ranged from −20 mV to −50 mV and were similar to those reported by other investigators: Rask‐Madsen: −39 mV [13], Tomkins and Edmonds: −34 mV [15], Beevers et al : −35 mV [16], Rampton et al : −50 mV [17] and Sandle et al : −37 mV [18] (present study: −43.5 mV). Our technique, with a subcutaneous electrode, is currently used for pd measurements at the intestinal or gastric level where mean pd is between −35 and −45 mV.…”
Section: Discussionsupporting
confidence: 89%
“…In control subjects, the basal values of rectal pd generally ranged from −20 mV to −50 mV and were similar to those reported by other investigators: Rask‐Madsen: −39 mV [13], Tomkins and Edmonds: −34 mV [15], Beevers et al : −35 mV [16], Rampton et al : −50 mV [17] and Sandle et al : −37 mV [18] (present study: −43.5 mV). Our technique, with a subcutaneous electrode, is currently used for pd measurements at the intestinal or gastric level where mean pd is between −35 and −45 mV.…”
Section: Discussionsupporting
confidence: 89%
“…Similar variability of endoscopic technique has been noted by Beevers, Morton, Tree & Young (1975), who found that the coefficient of variation for 10-20 repeated measurements on eight subjects ranged from 7.7 to 23%. Factors contributing to the poor precision of the endoscopic technique included damage and contamination of the agar with faeces, since the rectum was not washed out before each measurement.…”
Section: Determination Of Rectal Potential Difference In Mansupporting
confidence: 81%
“…As previously reported, both Aldo and progesterone are high during pregnancy, but the number of MR in MNL has been found normal in physiological pregnancy and low in PE (27), as reported in patients with PA (28). More interestingly the effector mechanism of Aldo, measured through the potential difference between rectal and oral mucosa, was normal in normal pregnancy and high in PE, as previously reported in PA (29). We hypothesized that some factor produced by the placenta blunts the effect of increased Aldo in normal pregnancy, but it lacks in PE, leading to the classical effects of Aldo excess, even though Aldo levels are reduced.…”
Section: Aldosterone In Pregnancy and Preeclampsiasupporting
confidence: 81%